Crohn's disease in people exposed to clinical cases of bovine paratuberculosis - Jones, PH; Farver, TB; Beaman, B; Çetinkaya, B; Morgan, KL (Cambridge Univ Press, 2006)
Mycobacterium avium subspecies paratuberculosis (Map), the cause of ruminant paratuberculosis, has been proposed as the causative agent of Crohn's disease. The objective of this study was to determine whether exposure to clinical cases of bovine paratuberculosis was a risk factor for Crohn's disease. A questionnaire was sent to dairy farmers living on premises where the occurrence or absence of clinical cases of bovine paratuberculosis had previously been determined. The prevalence of Crohn's disease was found to be similar to that reported in other studies in the United Kingdom and showed no association with bovine paratuberculosis. There was, however, a univariate association with geographical region. Ulcerative colitis showed univariate associations with age, frequency of contact with cattle and with smoking. The results do not support the hypothesis that Map plays a causative role in the aetiology of Crohn's disease.
Keywords: Inflammatory-Bowel-Disease; Polymerase-Chain-Reaction; Avium Subsp Paratuberculosis; Mycobacterium-Paratuberculosis; Johnes-Disease; Ulcerative-Colitis; Control Tissues; Prevalence; Susceptibility; Identification